Nalyze The Selfcare Model Based on Health Belief Model for Hypertention Patients Aged 45 To and Above In Malang - Milwati, Susi; Pitoyo, Joko (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
Hypertension is the most common cause of cardiovascular disease. Hypertension at the Mojolangu Health Center is in the top three based on patient visits. The purpose of this study was to analyze the Selfcare Model Based on Health Belief Model for Hypertension Patients aged 45 to and above in Malang City. The design used analytic survey with cross sectional approach, the sampling technique used was pruporsive sampling with a total sample of 140. The simple care variables were: values and attitudes, self-efficacy, social support. HBM variables are: vulnerability, severity, benefits, behavioral barriers and motivation. Statistical analysis using data processing techniques used is the CB-SEM method or Covariance Based SEM (CB-SEM), where CB-SEM is more intended as a method to confirm theory. The software used for CB-SEM processing is AMOS. The research found that the biggest total effect was from the variable self-care validation on motivation, which was 0.704, then the direct effect of the self-care validation on the benefits was 0.615, the smallest direct effect of value and attitude on severity was 0.011. This study recommends increasing HBM by paying attention to education and age so that self-care management can be better.